Menanamkan Kebiasaan Cuci Tangan 6 Langkah pada Anak di TK Wadi Fatimah Cirebon - Primadana Rizki; Tika Nuraini; Aulia Indah; Hani Tri Hidayani; Achmad Chudaivi; Siska Wulan; Tasya Fahira; Yani Nurhayani (Universitas Kristen Indonesia Toraja, 2025)
Health education in early childhood is an important step to establish a healthy lifestyle from a young age. One simple habit that needs to be taught is washing hands properly, especially before eating. This activity was carried out at Wadi Fatimah Kindergarten, Cirebon, to introduce and educate children about the importance of maintaining personal hygiene. The habit of washing hands properly is an effective step in preventing the spread of diseases, such as diarrhea and respiratory infections.This counseling teaches the steps of proper handwashing, such as wetting the hands, rubbing the palms and backs of the hands, cleaning between the fingers, rubbing the nails, cleaning the thumbs, and rinsing the hands thoroughly. To make it more interesting, the methods used include educational games and interactive videos, making it easier for children to understand and remember.The activities are designed to be child-friendly with simple language and interesting illustrations. Children are given the opportunity to practice directly, while parents and teachers are involved so that this habit can be applied at home and school. With this counseling, it is hoped to create a generation that is aware of the importance of hygiene, so that the overall health of the community can improve.